Inventarisasi Jenis Ular di Bukit Lawang Kecamatan Bahorok Kabupaten Langkat - Devi Octaviani; Mufti Sudibyo; Hanifah Mutia Z.N Amrul; Jamilah Nasution (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
The purpose of this research is to know what kind of snake and to find out the condition of the environment where he found the type of snake in Bukit Lawang, Bahorok Sub-district, Langkat regency of North Sumatera in December 2017 until January 2018. Sampling with exploratory method to all areas with potential snake. The results found 8 types of snakes grouped into 4 families, 3 types of columbridae 1 type of pareidae, 1 type of viperidae, and 1 type of lamprophiidae. Environmental temperature found at snake range of 25 ° C 32 ° C Chrysopelea pelia and Boiga dendrophila found in pH 7.0 Based on IUCN Red List and CITES Appendix snake found in Bukit Lawang Bahorok District Langkat Regency into Least Concern ( LC), and does not enter into appendix III, nor III in CITES, is not protected or animals threatened to exist until it can lead to extinction. The snake is a snake that spread widely and not endemic.